answersLogoWhite

0


Best Answer

You need to solve for a by getting it by itself. You do this by performing the same operation on both sides of the equation

3a + 2 = a -6

subtract 2 from both sides:

3a = a -8

subtract a from both sides:

2a = -8

divide both sides by 2:

a = -4

User Avatar

Wiki User

โˆ™ 2012-04-11 15:20:52
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards

J's study guide

2 cards

What is the name of Steve on minecraft's name

What is love

โžก๏ธ
See all cards

Steel Tip Darts Out Chart

96 cards

170

169

168

167

โžก๏ธ
See all cards

Add your answer:

Earn +20 pts
Q: What is the value for 3a plus 2 equal a - 6?
Write your answer...
Submit
Related questions

What is a plus 3a-2 plus 3a simplified?

7a minus 2, if "3a-2" means 3a minus 2. 3a plus 1 and 1-3rd in parenthesis times 3a, if "3a-2" means 3a squared. a plus 3a squared plus 3a = 1-3rd times 3a plus 3a times 3a plus 1 times 3a = 3a plus 1 and 1-3rd in parenthesis times 3a


If a equals 2 what is the value of 3a plus 6?

12


Simplify a plus 3a-2 plus 3a?

a + 3a - 2 + 3a. Add the a + 3a + 3a = 7a. You can't combine the -2 & 7a so the solution is: 7a - 2.


What is the answer to 2 plus 3A plus 9A?

2 + 3A + 9A = 2 + 12AThe numerical value depends on the value of 'A'.It changes whenever 'A' changes.


What is 3a plus 2 plus 3a plus 2?

It is 6a + 4


-2(3a plus 2) plus 2?

-2(3a+2)+2=


If 6a plus 3b equals 2 and b 4 then what is the value of 3a?

The solution for the value of 3a would be -3. The equation would be 6a + 3(4) = 2.


3a plus 2 plus 3a-5?

6a-3


3a(a plus 4)-2a plus 7?

It can be simplified to: 3a^2 +10a+7 or factored as (3a+7)(a+1)


What is x3 plus ax plus 3a plus 3x2?

x^3 + ax + 3a + 3x^2 = (x^3 + 3x^2) + (ax + 3a) = x^2(x + 3) + a(x + 3) = (x + 3)(x^2 + a)


How do you factor 9a2 plus 42at plus 49t2?

9a^2 + 42at + 49t^2 = (3a + 7t)(3a + 7t)


What is the value of a in 13a - 6 plus a equals 5a plus 3 plus 3a?

13a - 6 + a = 5a + 3 + 3a 13a + a - 5a - 3a = 3 + 6 6a = 9 6a/6 = 9/6 a = 3/2


C plus 3a-5?

-2


Does the a in both what expressions 3a - 9 equals 6 and 5a plus 2 equals 27 have the same value?

Yes.


What is 3a plus 2?

5a


What is a squared plus 3a-10?

a2+3a-10 = (a-2)(a+5) when factored


Simplify 5a plus 4b - 3a?

5a + 4b - 3a =(5a - 3a) + 4b =2a + 4b =2 (a + 2b)


Find the value of 3a plus 2b when a equals 6 and b equals 5?

3a + 2b = (3*6) + (2*5) = 18 + 10 = 283a+2b= (3x6)+(2x5)= 18+10=28


What is 6 - 3a2 plus 7 plus 4a - 5a plus 18?

6-3a**2+7+4a-5a+18 3a**2-1a+31


What is 3a2 plus 4a-4?

(a + 2)(3a - 2)


2 plus 3a plus 9a?

It is: 12a+2 when simplified


What are the factor of 9a2-24a plus 16?

(3a - 4)(3a - 4)


3a plus 2b - 6 - 2a - b plus 4?

= a + b - 2


What is the factored form of variable of a to the power of 2 plus 6a plus (-3a) minus 2 plus 4a?

idont know


What is 3aยฒ 3aยฒ?

3a^2 + 3a^2 = 6a^2 3a^2 - 3a^2 = 0 3a^2 x 3a^2 = 9a^4 3a^2 divided by 3a^2 = 1